1998
DOI: 10.1128/iai.66.12.5771-5776.1998
|View full text |Cite
|
Sign up to set email alerts
|

A Vaccine and Monoclonal Antibodies That Enhance Mouse Resistance toCandida albicansVaginal Infection

Abstract: We previously reported that a vaccine composed of liposome-mannan complexes of Candida albicans (L-mann) stimulates mice to produce protective antibodies against disseminated candidiasis. An immunoglobulin M (IgM) monoclonal antibody (MAb), B6.1, specific for a β-1,2-mannotriose in the complexes protects against the disease, whereas MAb B6 does not. In the present study, the vaccine and MAbs B6.1 and B6 were tested for the ability to protect againstCandida vaginal infection, established by intravaginal (i.vg.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(42 citation statements)
references
References 41 publications
0
38
0
4
Order By: Relevance
“…*Student's t test: normal women versus study subjects, P , 0.001. and none of which leading to clinical applications at this time. 26,27 Despite the accumulation of knowledge we have of underlying risk factors, we are still not able to cure or improve most women with RVC. During the last years, it has become increasingly clear that responses of different individuals to any given microorganism show considerable variability.…”
Section: Discussionmentioning
confidence: 99%
“…*Student's t test: normal women versus study subjects, P , 0.001. and none of which leading to clinical applications at this time. 26,27 Despite the accumulation of knowledge we have of underlying risk factors, we are still not able to cure or improve most women with RVC. During the last years, it has become increasingly clear that responses of different individuals to any given microorganism show considerable variability.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported the presence of three kinds of b-1,2 linkage-containing side chains in the mannans from Candida species [11][12][13][14][15][16][17]. Because the b-1,2-linked mannose unit is present among the pathogenic fungi only in the mannan of the genus Candida and the b-1,2 linkage-containing side chains behave as strong antigens, many workers [18][19][20][21][22][23][24][25] have produced monoclonal antibodies to b-1,2-linked mannose units to protect against candidiasis, for the serodiagnosis of candidiasis, or for the identification of mechanisms of Candida infection. Furthermore, studies have indicated the b-1,2-linked mannose units participate in the adherence of Candida cells to mammalian cells as the first step in infection [26][27][28].…”
mentioning
confidence: 99%
“…111 MAb B6.1 MAb B6.1 was a prophylactic and therapeutic IgMmonoclonal antibody that specifically targeted (1?2)b-mannotriose; it was formerly under development by LigoCyte Pharmaceuticals (Deerfield, IL, USA). [117][118][119][120][121][122] (1?2)-b-mannotriose is an acid-labile component of the phospholipomannan complex, expressed uniformly on the surface of C. albicans and other pathogenic nonalbicans Candida species, which displays adhesion. 117,118,120,121,123,124 The vaccine facilitates opsonophagocytic killing via the classical pathway of the complement system.…”
Section: Sordarinsmentioning
confidence: 99%